Assessment of Sea Ice Extent in CMIP6 With Comparison to Observations and CMIP5. Issue 9 (30th April 2020) - Shu, Qi; Wang, Qiang; Song, Zhenya; Qiao, Fangli; Zhao, Jiechen; Chu, Min; Li, Xinfang
Abstract: Both the Arctic and Antarctic sea ice extents (SIEs) from 44 coupled models in the Coupled Model Intercomparison Project Phase 6 (CMIP6) are evaluated by comparing them with observations and CMIP5 results. The CMIP6 multimodel mean can adequately reproduce the seasonal cycles of both the Arctic and Antarctic SIE. The observed Arctic September SIE declining trend (−0.82 ± 0.18 million km 2 per decade) between 1979 and 2014 is slightly underestimated in CMIP6 models (−0.70 ± 0.06 million km 2 per decade). The observed weak but significant upward trend of the Antarctic SIE is not captured, which was an issue already in the CMIP5 phase. Compared with CMIP5 models, CMIP6 models have lower intermodel spreads in SIE mean values and trends, although their SIE biases are relatively larger. The CMIP6 models did not reproduce the new summer tendencies after 2000, including the faster decline of Arctic SIE and the larger interannual variability in Antarctic SIE. Key Points: CMIP6 and CMIP5 models have similar performance in representations of Arctic and Antarctic sea ice extent trends and seasonality For both the Arctic and Antarctic, intermodel spreads of sea ice extent mean values and trends are smaller in CMIP6 than in CMIP5 models CMIP6 models did not reproduce the faster Arctic sea ice decline and larger Antarctic sea ice interannual variability in summer after 2000